Health Conditions in Adults With Cerebral Palsy: The Association With CP Subtype and Severity of Impairments - Jonsson, Ulrica; Eek, Meta N.; Sunnerhagen, Katharina Stibrant; Himmelmann, Kate (Frontiers in Neurology, 2021)
Aim: To determine the prevalence of common health conditions in adults with Cerebral Palsy (CP) and to identify associations with the CP subtype or the severity of impairments. Method: A population-based, cross-sectional study of 153 adults with CP born from 1959 to 1978 (87 males, 66 females; median age 48y 3mo, range 37–58 y; 41% with unilateral spastic, 36% bilateral spastic, 19% dyskinetic and 4% with ataxic CP). Data was gathered through interviews, physical assessments and medical record reviews. Results: The most common health conditions in adults with CP were pain 65%, upper gastrointestinal disorders 33%, dysphagia 29%, epilepsy 29%, and depression 27%. CP subtype was significantly associated with the presence of pain (p = 0.029), gastrointestinal (p < 0.001) and respiratory disorders (p = 0.006). A more severe physical impairment was associated with a higher prevalence of gastrointestinal disorders (p < 0.001), respiratory disorders (p < 0.001) and pressure ulcers (p < 0.001). Intellectual disability was associated with a higher prevalence of gastrointestinal disorders (p < 0.001), pneumonia (p = 0.001) epilepsy (p = 0.001) and pressure ulcers (p < 0.001), but with a lower prevalence of pain (p < 0.004) and hypertension (p = 0.043). Conclusion: The prevalence of several common health conditions is related to the CP subtype and severity of impairments, indicating that CP plays a role in the development of these health conditions. Follow-up of adults with CP needs to include not only impairments, but general health as well. Increased attention directed towards signs of gastrointestinal and respiratory disorders in individuals with either dyskinetic CP, GMFCS levels IV-V or intellectual disability, is recommended.